Digital Teaching Materials for Negotiation Texts Oriented Towards Creative Thinking for SMA/MA Students - Kasmawati; Gloriani, Yusida; Mascita, Dede Endang (PT Inovasi Pratama Internasional, 2025)
This research aims to develop digital teaching materials for negotiation texts that are attractive, can improve students' creative thinking abilities, and are easy for teachers and students to use, specifically for Class X SMA/MA students. The goal was to design digital teaching materials that enhance creative thinking and are practical for classroom implementation. This study employs a development research method based on the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods included interviews, observations, questionnaires for material experts, assessments from Indonesian language teachers, and material evaluation instruments. The result of the design and development process was a digital module in the form of a flippbook. This Flipbook features a cover page, module introduction with audio, examples of negotiation texts in both written and audio-visual formats, and exercise questions for learning evaluation provided via Google Forms. The module aims to improve students' creative thinking abilities, as assessed through their negotiation text writing processes. The research findings indicated that the digital teaching materials for negotiation texts received an average validation score of 80.6% from experts, categorizing them as worthy. The implementation results showed that students' learning outcomes improved after using the digital materials compared with before their use. Significant differences were noted in students' learning outcomes before and after the implementation of digital teaching materials. Consequently, it can be concluded that these digital teaching materials enhance students' understanding and improve their creative thinking abilities when learning negotiation texts